1994
DOI: 10.2307/2410362
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of the Pygmy-Forest Edaphic Subspecies of Pinus contorta Across an Ecological Staircase

Abstract: Patterns of allozyme variation within and between two of the subspecies of Pinus contorta were examined for the evolutionary relationship between them. In coastal northern California, these subspecies are parapatric. Pinus contorta ssp. contorta occurs on grassy coastal bluffs on the lowest and youngest of a sequence of five marine terraces; P. contorta ssp. bolanderi is endemic to a pygmy forest ecosystem that occurs on the increasingly older and harsher soils of the third, fourth, and fifth terraces. The soi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
33
0

Year Published

1997
1997
2012
2012

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(39 citation statements)
references
References 20 publications
6
33
0
Order By: Relevance
“…bolanderi (Parlatore) Critchfield: endemic to the Mendocino White Plains along the northern California coast. Evidence from genecological studies, provenance testing and biochemical markers supports the genetic affinities of the geographic races (Forrest, 1980;Wheeler and Guries, 1982;Rehfeldt, 1988;Ying and Liang, 1994;Aitken and Libby, 1994).…”
Section: Natural History and Ecology Of Lodgepole Pinementioning
confidence: 96%
“…bolanderi (Parlatore) Critchfield: endemic to the Mendocino White Plains along the northern California coast. Evidence from genecological studies, provenance testing and biochemical markers supports the genetic affinities of the geographic races (Forrest, 1980;Wheeler and Guries, 1982;Rehfeldt, 1988;Ying and Liang, 1994;Aitken and Libby, 1994).…”
Section: Natural History and Ecology Of Lodgepole Pinementioning
confidence: 96%
“…This might seem like a short time, especially for lodgepole pine (average generation time probably exceeds 100 years; e.g., Muir 1993), to evolve substantial differences. However, rapid and extensive evolution of quantitative traits, including cone structure, has occurred in other populations of lodgepole pine (Aitken and Libby 1994;Xie and Ying 1995). Moreover, many of the measured lodgepole pine cone traits are heritable.…”
Section: The Study Systemmentioning
confidence: 99%
“…Some authors reported significant correlations between habitat type and one or two allozyme loci (Heywood & Levin, 1985 and two references cited therein). Conversely, several studies failed to show allozymic differentiation among ecological races (Westerbergh & Saura, 1992;Freiley, 1993;Aitken & Libby, 1994) and concluded, under the implicit assumption that allozyme loci are neutral, either that ecological separation was too recent for drift to have promoted allozymic divergence or that the latter had been prevented by sufficient gene flow. Similarly, studies comparing variation at allozyme loci with that at morphometric or other genetically controlled traits have not consistently shown an association among the different types of traits (Hamrick, 1989).…”
Section: Ecotypic Differentiationmentioning
confidence: 99%